The Role of Cultural Capital Sports Oriented on Workersâ Participation in the Newspaper in Tehran, Iran - Abbas, Gholizadeh; Khabiri, Kaveh; Sepideh, Mehraein; Mehrad, Aida (Journal of Educational, Health and Community Psychology, 2017)
AbstractÂ This study examined the role of cultural capital sport oriented on workers participation. The active presence of workers in different workplaces is very significant; additionally, consider their physical health is so imperative. Moreover, distinguishing the effective factors that can increase the amount of workersâ physical health and persuade them to exercise is essential; also, lack of attention to them leads to several difficulties. In the study, focused on 400 workers who worked foÂ r the newspaper in Tehran, Iran. One questionnaire for assessing demographic factors and cultural capital sport oriented were used. Findings of the study showed that Â cultural capital sport oriented have significant relationship with workersâ participation. Also, body image determined as the first reason for sport among workers. In overall, the sport has a noticeable role in workersâ life and it can grow their mind and body health. In this regard, the head of workers should be developed some methods for introducing workers to the sport; likewise, determined valuable programs for them to increase physical power and growing muscles.Â Â Keyword: Cultural Capital, Physical Education, Sport, WorkersâÂ Â